Pengaruh Media Pembelajaran Colourfull Wordwall Terhadap Kemampuan Literasi Anak Usia 5-6 Tahun - Ramadani, Nur Husna; Azizah Amal; Ilyas, Sitti Nurhidayah (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2025)
This study aims to determine the effect of Colorful Wordwall media on the literacy skills of 5-6 year old children at Kindergarten Multazam, Gowa Regency. The research approach used is a quantitative approach with a quasi-experimental research type. The sampling in this research is all children aged 5-6 years at Kindergarten Multazam. The sampling in this research is purposive sampling. The sample in this study consisted of 24 children, 12 children as the experimental group and 12 children as the control group. The data collection technique used is descriptive statistical analysis and non-parametric statistical analysis using the Wilcoxon Sign Rank Test. Based on the research results, it can be concluded that the literacy skills of children given treatment using Colorful Wordwall media in the experimental group were better than the control group. The results of the data analysis showed an increase in the average in the experimental group of 9.58, while in the control group it was 8.66. The test results showed sig. (2-tailed) 0.002 < 0.05, so Ho is rejected and H1 is accepted. Thus, it can be concluded that colorful wordwall media has a significant effect on the literacy skills of 5-6 year old children at Kindergarten Multazam, Gowa Regency.